Investigation of speech perception for patients with a cochlear implant supported with a hearing aid - M. Niewiarowicz; O. Stieler; D. Komar (Archives of Acoustics)
The investigations were carried out for 5 listeners with a cochlear implant, 2 male and 3 female at implantation age 13–62 years. The deafness for 4 subjects was recognized as postlingual and for 1 – as perilingual. All listeners were using the hearing aid on the opposite ear to the implant. The speech intelligibility was determined in two cases: when transmission was only via the implant and when the hearing aid was also used. Additionally, the ability of discrimination of male and female voices was performed. The presentation of tests was conducted for three angles (0$^{°}$, −90$^{°}$ and+90$^{°}$) in relation to the listener’s head for the levels equal to 50, 65 and 80 dB SPL. The Polish monosyllabic word tests (PRUSZEWICZ et al., [4]) were applied. The improvement of the speech intelligibility was affirmed when the process of hearing via the implant was supported with a hearing aid. The particularly essential differences in the speech intelligibility was observed for angle +90$^{°}$ (HA-side). The results obtained in the investigations show that acoustic compensation in the range of remaining audibility field in a great degree supports electrical hearing.